Supporting linkage facilitators working with persons with opioid use disorder: challenges, advances, and future directions - Drazdowski, Tess K.; Coetzer-Liversage, Anthony P.; Stein, L. A. R.; Tilson, Martha; Watson, Dennis P.; Hoffman, Lauren A.; Hogue, Aaron; Castedo de Martell, Sierra; Hagaman, Angela Marie; Greene, R. Neil; Satcher, Milan F.; Hibbard, Patrick F.; et al. (Frontiers in Public Health, 2025)
This narrative review explores the evolving role of linkage facilitation (LF) in supporting persons with opioid use disorder (OUD) including both the organizational strategies to initiate and sustain LF services and strategies to support the LF workforce. Drawing on expert consensus and iterative review by an interdisciplinary author team, we synthesized relevant literature from diverse fields using a narrative review approach. Organizational strategies include: ensure leadership support, engage community partners and tailor services, consult with those already delivering LF services, provide adequate pay and career advancement opportunities, establish role clarification, and create official documentation of LF services. Strategies to support the LF workforce include: ensure comprehensive training and continuing education, provide robust supervision, encourage self-care, and establish quality/fidelity standards. Recommendations for advancing the profession include enhancing training for both LFs and supervisors, establishing centralized resource libraries, and tailoring support for diverse OUD-affected populations. This review advocates for the development of best practice guidelines, practical evaluation tools, and a collaborative resource-sharing hub to ensure long-term LF workforce sustainability and improved outcomes for those served.